Pathogens and Pests Threatening Plantation Forestry in Zimbabwe. Issue 2 (2nd October 2017) - Jimu, L.; Mujuru, L.
ABSTRACT: The Zimbabwean forestry industry, which contributes significantly to the economy, was introduced in the 1940s and is dominated by Pinus spp., Eucalyptus spp . and Acacia mearnsii De Wild. This paper assembles and consolidates literature on diseases and pests of forest plantations to serve as a foundation for management and future studies. Most of the outlined diseases and pests have been known since the early days of forest plantations (i.e. the 1960s) whilst some are recent, signifying their increasing importance to the forest industry. Pinus spp ., Eucalyptus spp . and A . mearnsii are affected by pathogens and pests originating from the native areas of the hosts while the origins of others are not known. Disease outbreaks resulted in discontinuous cultivation of Eucalyptus globulus Labill. and Pinus radiata D. Don. that were important species in eastern and southern Africa. Forest health issues impacting on forest production are poorly understood and there is an urgent need to implement a structured forest health survey program and appropriate support to identify current and emerging pest and disease issues. Additionally, this information is important to support the forestry seed and timber export program.